Why Plato wrote - Allen, Danielle S., 1971- (Blackwell Bristol lectures on Greece, Rome and the classical tradition., 2010)
Why Plato Wrote argues that Plato was not only the world's first systematic political philosopher, but also the western world's first think-tank activist and message man. Shows that Plato wrote to change Athenian society and thereby transform Athenian politicsOffers accessible discussions of Plato's philosophy of language and political theory.